Bisar 3.0 for Analytical Road Pavement Design: Bisar 3.0 untuk Desain Jalan Beraspal Analitis - N. Riwibowo; Prambudi, Wahyu Tri; Cahyaningrum, Fibia Sentauri; Ariyanti, Menik; Rizki, M. Alvan (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Safe and comfortable road pavement is a fundamental requirement, yet most designs rely on empirical methods that limit the ability to analyze detailed structural behavior. Specific Background: Analytical methods allow comprehensive evaluation of pavement layer strength, enabling faster and more precise calculations. Knowledge Gap: Limited studies have applied Bisar 3.0 guided by the Nottingham Design Method to calculate strain and service life in pavements using CTB (Concrete Treated Base) and Class B aggregate layers. Aim: This study applies the Bisar 3.0 program to determine road service life under fatigue cracking and permanent deformation criteria. Results: Calculations show analytical methods predict a longer service life ( ±20 years) than empirical methods. Higher foundation stiffness and low average daily traffic reduce service life, and fatigue cracking criteria indicate a longer lifespan than permanent deformation. Novelty: Integration of Bisar 3.0 with Nottingham Design Method for precise service life estimation provides a detailed analytical approach rarely applied in road pavement studies. Implications: Findings support engineers in optimizing pavement design, selecting appropriate layer materials, and predicting long-term road performance more accurately. Highlights: Analytical design predicts longer road service life than empirical methods Fatigue cracking lifespan exceeds permanent deformation lifespan Bisar 3.0 enables rapid and precise calculation of pavement layer strains Keywords: Road Pavement, Analytical Method, Bisar 3.0, Nottingham Design Method, Service Life